Ethics and law in Mexico: Reflections on their relationship in the due process - Juárez Quezada, Guadalupe (2023)
This article discusses the importance of ethical legal rules and actions of judges and civil servants in Mexico for the evidentiary due process. It focuses on ethics in law, particularly in the administrative public function. The research applies the deductive method, connecting the philosophical theory and procedural aspects. Documentary sources such as national legislation and legal literature are used to support arguments. The aim is to justify the need for codes of ethics in the public power, primarily in the administrative public function. The conclusions confirm this statement.